The Stone Age of Indonesia - van Heekeren, H. (0284cf41-971b-46f2-b479-bee12c2754e0, 1957)
This first edition of The Stone Age of Indonesia has been replaced by the second edition, which is published as Volume 61 (1972; ISBN 9024713005) in the series Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde.